Analisis Kebutuhan Tenaga di Instalasi Farmasi RS Universitas Muhammadiyah Malang Tahun 2016 - Noor Annisa Susanto; Muhammad Mansur; Thontowi Djauhari (Universitas Muhammadiyah Yogyakarta, 2017)
The success from standard of pharmaceutical service at Muhammadiyah University Hospital is supported by the availability of human resources. Therefore it is necessary to analyze the needs of pharmaceutical personnel based on workload. This research is a descriptive research with primary data collection method through observation and interview and secondary data in the form of monthly and annual report. The WISN ratio is calculated by comparing conditions in the field with WISN calculation results. The result of this research is WISN ratio 0,4. The ratio <1 mean that the current amount of human pharmacy resources smaller than the required. It show the condition of IFRS UMM currently lack of pharmaceutical human resources.